Excitatory and Inhibitory Neurons in the Hippocampus Exhibit Molecularly Distinct Large Dense Core Vesicles - Ramírez-Franco, José J.; Munoz-Cuevas, Francisco J.; Luján, Rafael; Jurado, Sandra (Frontiers in Cellular Neuroscience, 2016)
Hippocampal interneurons comprise a diverse family of inhibitory neurons which function is critical for fine information processing. Along with gamma-aminobutyric acid (GABA), interneurons secrete a myriad of neuroactive substances via secretory vesicles which molecular composition and regulatory mechanisms remain unknown. In this study, we have carried out an immunohistofluorescence analysis to describe the molecular content of vesicles in distinct populations of hippocampal neurons. Our results indicate that phogrin, an integral protein of secretory vesicles in neuroendocrine cells, is highly enriched in parvalbumin-positive interneurons. Consistently, immunoelectron microscopy revealed phogrin staining in axon terminals of symmetrical synapses establishing inhibitory contacts with cell bodies of CA1 pyramidal neurons. Furthermore, phogrin is highly expressed in CA3 and dentate gyrus interneurons which are both positive for PV and neuropeptide Y. Surprisingly, chromogranin B a canonical large dense core vesicle marker, is excluded from inhibitory cells in the hippocampus but highly expressed in excitatory CA3 pyramidal neurons and dentate gyrus granule cells. Our results provide the first evidence of phogrin expression in hippocampal interneurons and suggest the existence of molecularly distinct populations of secretory vesicles in different types of inhibitory neurons.